ANALISIS EKONOMI MASYARAKAT MELAYU DI DUSUN MADANG KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN - Setianto, Adi; Maharani, Evy; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is  to determine the income level of Petalangan Malay community in Madang Village Pangkalan Lesung District. This research conducted by purposive sampling of 20 Petalangan Malay community samples determined using snowball sampling method. The result showed that.The income level of Petalangan Malay community in Madang Village consists of father income, Mother income, Child income. Father income who above regional minimum pay (UMR) as many as 13 respondents from 20 respondents (65.00%). Father livelihood consists of rubber farmer, palm farmer, farmworker, official employee, toke, civil servant and construction worker. Mother income who above regional minimum pay (UMR) as many as 4 respondents from 20 respondents (20.00%). Child income from 20 respondents there were 14 respondents (70.00%) who have not income and 6 respondents (30.00%) who have income under regional minimum pay (UMR), because the childs only working to helped farmers.     Key words: Petalangan Malay community, Income level, father income, Mother income, Child income.